Obtaining party positions on immigration in Switzerland: Comparing different methods - Ruedin, Didier (My University, 2013)
The position of political parties on policy issues is crucial for many questions of political science, including studies of political representation. This research note examines different methods for obtaining party positions on immigration in retrospective. Party positions are obtained using pooled expert surveys, manual coding of party manifestos with a conventional codebook, manual coding of manifestos using check-lists, and automatic coding of manifestos using Wordscores and a dictionary of keywords respectively. In addition, positions from a media analysis and a retrospective evaluation of researchers in the field of immigration are used. The results suggest that most methods differentiate the same order of party positions. While there are high correlations between many methods, the different methods tend not to agree on the exact positions. The automatic dictionary approach does not seem to measure party positions reliably.